Retrospective Evaluation of C-reactive Protein for Ruling Out Infection After Cesarean Section - Enengl, Sabine; Oppelt, Peter; Mayer, Richard Bernhard; Brandlmayr, Elisabeth; Trautner, Philip Sebastian (Geburtshilfe und Frauenheilkunde, 2024)
Infection after cesarean section is a major contributor to maternal morbidity. Measurement of C-reactive protein (CRP) is a laboratory test frequently conducted to rule out or confirm postoperative infection. The present study aimed to evaluate whether CRP is a suitable tool for ruling out infection after cesarean section and whether there are any reliable cut-off values.2056 patients with cesarean section (CS) over a 3-year period were included in a retrospective analysis. Outcome parameters and risk factors for postoperative infection were collected. CRP values from preoperative and postoperative tests were compared. Cut-offs for ruling out infection were assessed.Among 2056 CSs, postoperative infection occurred in 78 cases (3.8%). The prevalence of infection in emergency CS was lowest, at four out of 134 (2.9%), and the highest prevalence was seen in secondary CS, at 42 of 903 (4.6%; p = 0.35). CRP values in the infection group were significantly higher (preoperative, 1.01 mg/dl vs. 0.62 mg/dl; day 1 postoperative, 7.91 mg/dl vs. 6.44 mg/dl; day 4 postoperative, 8.44 mg/dl vs. 4.09 mg/dl; p = 0.01). A suitable cut-off value for ruling out infection was not identified.Although CRP values were significantly higher in the infection group, the clinical relevance of this appears to be negligible. CRP testing does not appear to be a reliable tool for diagnosing or ruling out postoperative infection.
Keywords: C-reactive protein; CRP; cesarean section; infection; surgical site infection